ACCOUNTANT PROFESSION: FUNCTION, ROLE AND HIS ORDER DURING THE INDUSTRIAL REVOLUTION 4.0 - Candra, Revi; Wahyuni, Elmiliyani; Shobirin, Khairulis (2021)
In the Industrial revolution 4.0, there was a remarkable shift in various fields of science and profession, for which the workings and practices of accountants needed to be changed to improve the quality of services and the use of cloud computing as well as global expansion through online communication. Accounting and the accounting profession must keep up with the times, should not be left behind and abandoned. Accounting and accounting professions in addition to having a vision in the future – predictive, also have to adapt to the changing system that develops, so that it can connect with the outside world and provide benefits and continue to be relevant and present. The digital industry era was able to eliminate 1 to 1.5 million jobs from the range of 2015-2025, due to human factors replaced with automation machines globally. The challenge of today's professional accountants is to find the right formulation to maintain accountability in the face of increasingly difficult technological developments and innovations. Surely the greater the risk of not being able to be mapped. Conventional asset assessment will shift to intangible asset assessment along with the development of technology and innovation. The role of professional accountants unravels the problem by providing solutions with independence and love for the country into clarity to contribute to realizing a prosperous society, therefore accountants must be professional by improving expertise. This research aims to explore the Functions, Roles, and Challenges of the accountant profession in Industrial Revolution 4.0